Potential impact of HPAI on Ghana: a multi-market model analysis - Schmitz, Christoph; Roy, Devesh (International Food Policy Research Institute, 2009)
Like in most African countries, the livestock sector is an important part of the economy in Ghana. At an aggregate level it contributes to about 7 percent of Ghana’s GDP and more than 40 percent to the agricultural GDP (Aning et al. 2008). Within the livestock sector, poultry comprising chicken, ducks, guinea fowls, turkeys, and ostrich constitutes an integral part of the rural farming system. Though Ghana has some commercial and semi commercial large farms, most poultry production – an estimated 60 to 80 percent – takes place at a smaller scale, where chickens are free range with minimal use of purchased inputs. Ghana also imports poultry. Poultry meat imports, particularly chicken, have increased more than four times between 2000 and 2005, and they account for around 75 percent of total consumption (Aning et al. 2008).